(untitled) (Asian Journal of Ethnobiology, 2023)
Abstract. Ali S, Munazir M, Sher H, Qureshi R, Akram M. 2023. An ethnobotanical study of aromatic medicinal plants of Swat Valley, Pakistan. Asian J Ethnobiol 6: 163-172. Plants play a key role in local medicines and are a source of income, as in the case of Swat, Pakistan, which is rich in medicinal plants coupled with rich in the practice of traditional knowledge and diverse cultures. So, the present study aimed to record the cultural uses of aromatic medicinal plants commonly used as medicines by herbalists from remote areas in Swat Valley. The survey was carried out in 2021 and 2023 using a semi-structured questionnaire with a total of 106 people were interviewed. A total of 33 aromatic medicinal plant species belonging to 30 genera and 14 families were identified and recorded. Lamiaceae was the most commonly used plant family (33%), followed by Apiaceae (18%), Rutaceae (9%), Zingiberaceae (6%), and Myrtaceae (6%). Herbs were commonly used for herbal recipes with 23 species (69%), followed by shrubs (12%), trees (15%), and climbers (3%). Shoots and leaves (30%) were the most commonly used parts of the plants, followed by fruits (18%), seeds (15%), bulbs (6%), rhizomes, bark, and needles (3%). In terms of mode of application, powder was the most common mode (42%), followed by dried (30%), infusions (27%), decoctions (24%), crushing (6%), and heating (3%). The highest Relative Frequency of Citation (RFC) was Skimmia laureola with 0.84, while Anisomeles indica had the lowest RFC (0.13). In terms of Fidelity Level (FL), Zingiber officinale had the highest FL (83%), while Sium latifolium had the lowest FL (13%). The recorded aromatic medicinal plants are mostly used to treat stomach problems. It has also been observed that elderly people are more knowledgeable than younger ones. Therefore, the present study suggests that these plants should be screened for new compounds linked to their reported use in the development of new therapeutics.